REVOCATION OF HADHANAH AT THE PEKANBARU HIGH RELIGIOUS COURT (DECISION ANALYSIS No.26/ Pdt.G /2023/ PTA.Pbr) - Saragih, Chantika Andini; Khalid, Khalid (LPPM STIH Putri Maharaja, 2023)
The purpose of this writing is to know and understand the methods and concepts used by judges to determine the revocation of child custody (hadhanah). The method used in this study is normative legal research. Legal research is a method of examining documentary studies, which includes the use of several materials such as court decisions, legal theories, regulations and laws. The topic of discussion this time is the analysis of the judge's decision regarding the revocation of child custody at the Pekanbaru High Religious Court decision No.26/Pdt.G/2023/PTA.Pbr as the subject of this research. The results of this analysis show that the method for taking hadhanah in the Pekanbaru Religious Court's decision was carried out by the Pekanbaru Religious High Court's panel of judges while taking into account the signs in its decision, especially because the benefit of the life of a child who is not yet 12 years old is the right of the mother. Regarding this matter, according to Article 105 of the Compilation of Islamic Law, it explains in more detail that if there is separation between husband and wife, among other things (1) custody of children under 12 years of age is the mother's right.